KOKAN LITERARY ENVIRONMENT AND LITERATURE OF THE NATIONAL RENAISSANCE PERIOD. - Aliyeva Nargiza Ravshanjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Kokan literary environment began to form in the first half of the 18th century. The most flourishing and developed period corresponds to the time when Amir Umar Khan (1810-1822) ruled. The fact that Amir gathered many poets, historians, literary scholars and held creative meetings in his presence shows how high the literary environment has reached, in addition, Umar Khan also guided artists, calligraphers, painters, and music experts. The period of national renaissance (modernism period) in our country began in 1865 and brought the people into the world of "new thinking". Great and unrepeatable works were created. Of course, the literature of Uzbekistan occupies a very large place in these centuries.